SUCCESS RATES OF THROMBECTOMY IN STEMI PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION - SAQI , MAUR; BUBAKAR , M; FAROOQ , M; ASHRAF , MW; ASLAM , M; FAROOQ, F (Biological and Clinical Sciences Research Journal, 2024)
Percutaneous coronary intervention (PCI) is a standard treatment for ST-segment elevation myocardial infarction (STEMI) patients. The role of thrombectomy as an adjunct to PCI remains debated, with conflicting evidence regarding its benefits and associated risks. Objective: This study aimed to compare the outcomes of patients receiving PCI with and without thrombectomy in managing STEMI, evaluating key parameters such as mortality, re-infarction, heart failure, cardiogenic shock, renal dysfunction, bleeding complications, stroke, and hospital stay duration. Methods: This cross-sectional study included 100 patients who met the inclusion criteria. Patients were divided into two groups: Group A (n=50) underwent PCI alone, and Group B (n=50) received PCI with adjunctive thrombectomy. Outcomes were compared between the two groups, including mortality, re-infarction, cardiac failure, cardiogenic shock, renal dysfunction, bleeding complications, stroke, and hospital stay. Statistical analysis was performed using appropriate tests, with significance at p < 0.05. Results: Of the 100 patients, 62% were male, and 38% were female. The mean age of patients in Group A was 54.19 ± 12.62 years, while in Group B, it was 55.22 ± 13.51 years. The mean BMI in Group A was 25.5 ± 3.16 kg/m², compared to 24.35 ± 5.75 kg/m² in Group B. Diabetes was present in 54% of Group A and 44% of Group B, and a history of smoking was reported in 38% of Group A and 34% of Group B. There was no significant difference in mortality between the two groups. However, renal dysfunction occurred in 1 patient in Group A and five in Group B (p = 0.03). Heart failure was noted in 3 patients in Group A and 6 in Group B (p = 0.002). Significantly more cases of stroke, excessive bleeding, and renal dysfunction were observed in Group B (PCI with thrombectomy) compared to Group A. Conclusion: Patients undergoing PCI with thrombectomy were at higher risk of developing complications, including stroke, renal dysfunction, and heart failure, compared to those receiving PCI alone. Although there was no significant difference in mortality between the two groups, the increased risk of post-procedure complications in the thrombectomy group suggests that careful patient selection is crucial for optimizing outcomes.